Effect of the cross-linker on the general performance and temperature dependent behaviour of a molecularly imprinted polymer catalyst of a Diels-Alder reaction - Henschel, H.; Kirsch, N.; Hedin-Dahlström, J.; Whitcombe, Michael J.; Wikman, S.; Nicholls, I. A. (Cranfield University, 2011)
Here we present a series of molecularly imprinted polymers capable of catalysing the Diels-Alder reaction between benzyl 1,3-butadienylcarbamate (1) and N,N- dimethyl acrylamide (2). The polymer systems studied here demonstrated an unusual cross-linker and temperature dependent behaviour, namely that polymer catalysis of the Diels-Alder reaction was lower at elevated temperature, in contrast to the solution reaction. Furthermore, not only was the catalytic activity significantly influenced by the choice of cross-linker, but in a similar fashion also the extent of the temperature effect, indicating a close relationship between catalysis and the observed inhibition. Molecular dynamics simulations of both the polymer systems studied were used to provide insight into the molecular background of transition state stabilisation, and differences in properties of the systems based on different cross-linkers.
Keywords: Diels–Alder reaction, Molecularly imprinted polymer, Molecular dynamics simulation, Plastic antibody, Transition state analogue